2023
DOI: 10.4084/mjhid.2023.006
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Homeostasis and Αssessment of Β-Cell Function by 3-Hour Oral Glucose Tolerance (Ogtt) in Patients With Β-Thalassemia Major With Serum Ferritin Below 1,000 Ng/Dl: Results From a Single Icet-a Centre

Abstract: Aims: The primary aim of this study was to evaluate retrospectively the glucose homeostasis and surrogate indexes of insulin sensitivity and resistance, during a 3-hour oral glucose tolerance test (OGTT), in β- thalassemia major patients (β-TM) with serum ferritin (SF) below 1,000 ng/mL. Patients and methods: The retrospective cohort study evaluated the medical records of 24 β-ΤΜ patients from 2010 to 2022. Αt the year of study the mean age of patients was 31.0 ± 4.1 (20-37.11) years; 13 (54.1%) were fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Impaired glucose metabolism in β-thalassemia implicates increased insulin resistance, glucose intolerance, and diabetes mellitus (DM) [4]. In Table 1, the prevalence of DM in β-thalassemia is reported and varies from 0% to 35% [10][11][12][13][14][15]. Risk factors for impaired glucose metabolism include older age, high body mass index (BMI), elevated mean ferritin serum levels, and history of splenectomy [11,12,[16][17][18].…”
Section: Impaired Glucose Metabolism and Diabetes Mellitusmentioning
confidence: 99%
“…Impaired glucose metabolism in β-thalassemia implicates increased insulin resistance, glucose intolerance, and diabetes mellitus (DM) [4]. In Table 1, the prevalence of DM in β-thalassemia is reported and varies from 0% to 35% [10][11][12][13][14][15]. Risk factors for impaired glucose metabolism include older age, high body mass index (BMI), elevated mean ferritin serum levels, and history of splenectomy [11,12,[16][17][18].…”
Section: Impaired Glucose Metabolism and Diabetes Mellitusmentioning
confidence: 99%
“…Therefore, better management of iron overload in β-thalassemic/pre-diabetics may reduce the risk or delay the onset of diabetes in this patient group. A previous study measured the prevalence of glucose dysregulation in β-thalassemia patients across different countries 25 revealed that transfusion-dependent thalassemia patients show a higher prevalence of glucose dysfunction (31.0%) relative to non-transfusion-dependent thalassemia patients (12.1%).…”
Section: Introductionmentioning
confidence: 99%